2018 20th International Conference on Transparent Optical Networks (ICTON) 2018
DOI: 10.1109/icton.2018.8473872
|View full text |Cite
|
Sign up to set email alerts
|

Connection Provisioning in Spectrally-Spatially Flexible Optical Networks with Physical Layer Considerations

Abstract: This paper presents efficient connection provisioning techniques for spectrally-spatially flexible optical networks (SS-FON) utilizing multicore fibers (MCFs) when physical layer effects are taken into consideration. To account for the physical layer effects, two approaches are presented that are used to establish a given set of demands. One approach is to provision the requests that have acceptable quality-of-transmission (QoT) assuming a fully-loaded network for specific modulation formats, so that in the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…It is shown that the latter problem is NP-hard even for a single link, and ILPs as well as heuristic approaches are proposed to solve the problem for large traffic instances. In addition, authors in [29]- [34] solve the RSCA problem, while also considering the crosstalk effect, in order to improve the performance of SDM flexible optical networks with MCFs. In a similar vein, authors in [30] propose a core prioritization policy based on the MCF's architecture to reduce crosstalk by avoiding the utilization of adjacent cores.…”
Section: Related Workmentioning
confidence: 99%
“…It is shown that the latter problem is NP-hard even for a single link, and ILPs as well as heuristic approaches are proposed to solve the problem for large traffic instances. In addition, authors in [29]- [34] solve the RSCA problem, while also considering the crosstalk effect, in order to improve the performance of SDM flexible optical networks with MCFs. In a similar vein, authors in [30] propose a core prioritization policy based on the MCF's architecture to reduce crosstalk by avoiding the utilization of adjacent cores.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, a flexible grid is implemented with channel spacing of 12.5GHz which results in a total of 320 spectrum slots for each link in the network with a baud rate of 10.7 Gbaud for each frequency slot. Further, the Telefonica network [17] with 30 nodes and 56 bidirectional links is used for all experiments. In all cases, demands are randomly generated using a uniform distribution for all s-d pairs, where each demand size varies from 10 to 100 Gbps.…”
Section: Performance Evaluationsmentioning
confidence: 99%